Changes and Influencing Factors of Cognitive Impairment in Patients with Breast Cancer. (28th October 2021) - Cui, Huixia; Shi, Xusheng; Song, Xiaoxiu; Zhang, Wenlu
Abstract : Objective . To investigate the changes in cognitive function and its influencing factors in patients with breast cancer after chemotherapy, to provide a scientific basis for further cognitive correction therapy. Methods . In this study, general information on age, marital status, and chemotherapy regimen was collected from 172 breast cancer chemotherapy patients. 172 patients with breast cancer undergoing chemotherapy were investigated by convenience sampling method, and the subjects were tested one-on-one using the Chinese version of the MATRICS Consensus Cognitive Battery (MCCB) computer system. Results . The mean value of standardized t-value of cognitive function and its abnormal dimensions in breast cancer patients undergoing chemotherapy were MCCB total cognition (66.3%, 36.99 ± 13.06, abnormal), working memory (73.3%, 36.84 ± 10.25), attention and alertness (70.3%, 37.20 ± 12.50), social cognition (65.1%, 39.54 ± 10.17), and visual memory (61.6%, 42.19 ± 9.38). A comparison of cognitive function among breast cancer chemotherapy patients with different demographic characteristics showed that differences in place of residence, educational level, monthly income, timing of chemotherapy, chemotherapy regimen, and chemotherapy times may be associated with abnormal cognitive function. Further multiple linear regression analysis was performed and the results showed that there was a linear regression between literacy, number of chemotherapy sessions, monthly personal income, and cognitive function. Conclusion . Cognitive impairment is common in patients with breast cancer after chemotherapy. Nurses should pay attention to the cognitive function changes and intervention of patients with breast cancer after chemotherapy, to prevent the changes of cognitive function and promote the rehabilitation of patients.